Analisis kesulitan membaca aksara Jawa nglêgêna pada peserta didik kelas III sekolah dasar ditinjau dari perspektif psikolinguistik - Dyah Maharani; Joko Daryanto (Universitas Sebelas Maret, 2025)
This study aims to describe the difficulty of reading nglêgêna Javanese script reviewed from a psycholinguistic perspective. This study is a descriptive qualitative study with a case study approach. Data sources in this study include respondents/informants, the process of completing the test, and documents. Data collection was conducted using active participation interview techniques, tests, and documentation study analysis. Data analysis used Miles and Huberman's interactive analysis technique. The results of this study describe the difficulty of reading the nglêgêna Javanese script from a psycholinguistic perspective in the form of difficulties at the conceptualization stage (understanding the concept), formulation (thinking), and articulation (pronunciation). The difficulty in reading nglêgêna Javanese script at the conceptualization stage lies in the activity of distinguishing the form/morpheme of nglêgêna Javanese script, understanding that 1 nglêgêna Javanese script represents 1 syllable, and understanding the concept of